2016
DOI: 10.3109/19401736.2015.1127362
|View full text |Cite
|
Sign up to set email alerts
|

The first taxonomic revaluation of the Iranian water frogs of the genus Pelophylax (Anura: Ranidae) using sequences of the mitochondrial genome

Abstract: The Eurasian water frog species and their geographic ranges have undergone considerable changes in the last four decades, but the Iranian populations have largely remained unknown. All the Iranian populations of water frogs, despite their vast distribution range have attributed to a single species: Rana ridibunda. In order to understand the phylogenetic relationships and taxonomic status of water frogs of Iran, we collected samples from many populations across the country and used the mitochondrial DNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…However, Pesarakloo et al (2018) suggested all water frogs from northwestern, western and southwestern populations from Iran (identical to the MHG6d population in Akin et al In order to resolve the discordant and complex data pertaining to the taxonomy of Pelophylax ridibundus sensu lato in Iran, we need to survey genetic differentiation of these populations including samples not only from across Iran but also surrounding countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Pesarakloo et al (2018) suggested all water frogs from northwestern, western and southwestern populations from Iran (identical to the MHG6d population in Akin et al In order to resolve the discordant and complex data pertaining to the taxonomy of Pelophylax ridibundus sensu lato in Iran, we need to survey genetic differentiation of these populations including samples not only from across Iran but also surrounding countries.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies (Pesarakloo et al, 2016) that have been conducted on the Iranian water frogs reinforced the possibility that two major clades are present. One of these clades includes western, northwestern and southwestern populations called P. bedriagae .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unidentified helminths recovered from 47 specimens of Pelophylax ridibundus (Pallas, 1771) (but see Pesarakloo et al, 2017) collected in the vicinity of Shiraz, Fars Province, Iran in 1972, were borrowed from the Canadian Museum of Nature Parasites Collection in 2016 by the author. Platyhelminthes were stained with Mayer’s paracarmine or Gomori´s trichrome, dehydrated, cleared in methyl salicylate, and mounted in Canada balsam.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, they are distributed from eastern Spain to western China, through Central Europe, the Balkans, the Anatolian Peninsula, the Caspian Region and Central Asia (Akin et al 2010). In the division between Central (Afghanistan, Iran, Turkmenistan, Uzbekistan) and Southern Asia, where the territory of Pakistan falls, three species are currently recognised: P. bedriagae, P. ridibundus and P. terentievi (Wagner et al 2016;Pesarakloo et al 2017;Showler 2018;Frost 2021).…”
Section: Introductionmentioning
confidence: 99%